(untitled) (Revista LIDER, 2021)
This article characterizes aspects belonging to the residential district, understood as a public space, territorial, fragmented of the city, that generates its dynamic starting from the proximity in social, cultural practices and from daily coexistences, but, at the same time, its non-uniform composition and identity weight give place to situations of conflict, segregation and inacceptance of new fragmentations.